Societies’ Funds Management System Using Blockchain - Jun Xiang Lau; Nur Ziadah Harun; Suziyanti Marjudi; Abd Samad Hasan Basari; Nur Amlya Abd Majid; Roziyani Setik (Multimedia University, 2026)
Indexed by MyCite (Tier 3)